Maqashid Sharia as a Framework for Innovation in Corruption Prevention - Sudarmanto, Eko; Kaswoto, Junet; Warto, Warto; Budiman, Mamdukh; Wahyono, Zubaidi (International Journal of Islamic Thought and Humanities, 2025)
This study examines the application of Maqashid Sharia as an innovation framework in corruption prevention. Corruption continues to be a major obstacle to good governance, harming public trust and socio-economic progress. Addressing this issue requires approaches that combine ethical principles with effective tools for monitoring and accountability. The study aims to evaluate the role of Maqashid Sharia in creating clean, transparent, and accountable governance. It also explores the integration of modern technologies, such as blockchain, with Maqashid Sharia to support a more effective monitoring system in the fight against corruption. The research method employed is a qualitative approach with descriptive analysis. Data was collected through a literature review, including articles, books, and other sources relevant to the concept of Maqashid Sharia and the innovation framework in corruption prevention. The results indicate that the application of Maqashid Sharia can enhance transparency, accountability, and justice in public resource management. Furthermore, the integration of technologies such as blockchain can strengthen efforts in corruption prevention by providing a more open and accountable system. However, challenges related to infrastructure and public understanding of technology must be addressed for the effective implementation of this approach.